(untitled) (Architecture Image Studies, 2025)
Since the beginning of civilization, the relationship between human beings and nature, natural phenomena, and natural texture have been a source of inspiration and focus of interest for artists, designers, and architects as well as for researchers and scientists. Accordingly, Mandelbrot, a mathematician, put forward the concept of fractal geometry as an extension of classical geometry with no conformity to its rules. Mandelbrot claimed that the concept of geometry was inadequate to explain the formal language, diversity, and cellular compositions of nature with the geometric axioms and proportions put forward by Euclid around 365-300 BC. Fractal geometry allowed an understanding of the formation of complex, chaotic, irregular, randomness, organic shapes and forms in nature and many natural phenomena. On the other hand, Bauhaus School introduced design disciplines in the 20th century, which were developed with industrialization. The basic design principles, which have complex and deep roots in the language of art, design and psychology, have succeeded in moving from thought to application and practice. With the simultaneous development of materials and technology, it has targeted and made it a necessity to exhibit concrete integrity and more scientific working discipline in order to reveal the designer’s artistic approach and imagination. This study included a characteristic analysis of 20 buildings that best reflect the principles of fractal geometry and design. It was considered that these principles would help a concrete design concept by making a matrix table study including their characteristic features.